The Relationship between Neutrophil-Lymphocyte Ratio and Ocular Manifestations in Children with Human Immunodeficiency Virus - Fithria Aldy (Medicinski glasnik, 2025)
ABSTRACT Context: Children with Human Immunodeficiency Virus (HIV) face elevated risks of systemic and ocular complications, potentially leading to blindness, particularly in developing countries where cases are rising. Aim: To investigate the association between neutrophil-lymphocyte ratio (NLR) and ocular manifestations in children with Human Immunodeficiency Virus (HIV) infection. Methods: This cross-sectional study involved 75 HIV-positive children aged 5-18 years at Yayasan Peduli Anak, Medan, Indonesia, from October to December 2023. Data were collected via interviews, comprehensive eye examinations (visual acuity, slit-lamp biomicroscopy, Schirmer test, indirect ophthalmoscopy), and recent NLR from medical records. Systemic cytomegalovirus (CMV) infection was assessed via CMV PCR. Sample size was calculated for correlation analysis (?=0.05, power=0.80, effect size=0.5). Results: Of 75 participants (56% male, median age 11.64 years), 88% had normal immune status. Mean antiretroviral therapy (ARV) duration was 9.56 years. Common ocular complaints included blurry vision (24%), red/itchy eyes (16%), and watery eyes (4%); no dry eye was reported. Anterior segment findings included conjunctivitis (6%), blepharitis (8%), and corneal scarring (4%); posterior segment findings included tigroid fundus/nasalization (4%) and retinal detachment (2%). Mean NLR was 1.76 in those with ocular manifestations (p=0.024). CMV PCR positivity was significantly associated with blurry vision (OR=6.63; p=0.015), red eyes (OR=4.75; p=0.049), corneal scarring (OR=16.00; p=0.044), and nasalization (OR=16.00; p=0.044). Conclusion: Elevated NLR was associated with ocular manifestations in pediatric HIV, particularly CMV-related complications. Regular eye screenings and ARV adherence are critical for early detection and prevention of vision-threatening conditions. Keywords: : antiretroviral therapy, Cytomegalovirus, eye diseases, inflammation, pediatrics
Keywords: Antiretroviral Therapy; cytomegalovirus; Eye Diseases; inflammation; Pediatrics